IMPORTANCE OF PICTURES BASED ON FAIRY TALES IN SPIRITUAL AND MORAL EDUCATION OF PRESCHOOL CHILDREN - Gaynazarova Gulbakhor Abdullayevna (Academia Science Repository, 2023)
The article presents the diagnostic technique "Fairy Tale", developed by the author and aimed at the study of one of the neoplasms of preschool age - the first ethical instances. Fairy tales are read to the child, according to which a conversation is then held with him.